Binding and loosing on earth: Evaluating the strategy for church disciplinary procedures proposed in Matthew 18:15-18 through the lenses of thinking and feeling - Francis, Leslie J. (HTS teologiese studies, 2019)
Matthew 18:15–18 proposed a disciplined strategy for dealing with disputes within the Matthean emerging Christian community. The present study was designed to test the theory, proposed by the SIFT approach to biblical hermeneutics, that reader interpretation of this strategy is influenced by the individual readers’ psychological type preferences. Participants attending two conferences in 2017 reflected on this strategy, working in groups that distinguished between feeling types and thinking types: 15 biblical scholars at the Summer School of the Urban Theology Unit, and 22 curates and training incumbents at a 3-day residential programme. Consistent with psychological type theory and with the SIFT approach to biblical hermeneutics, the feeling types found the whole tone of the passage uncomfortable and unsettling. The thinking types identified more readily with the Matthean strategy. These findings add weight to the reader perspective approach to the interpretation of scripture that takes the psychological type profile of the reader into account.